The Current Status of the Soybean-Soybean Mosaic Virus (SMV) Pathosystem - Liu, Jian-Zhong; Fang, Yuan; Pang, Hongxi (Frontiers in Microbiology, 2016)
Soybean mosaic virus (SMV) is one of the most devastating pathogens that cost huge economic losses in soybean production worldwide. Due to the duplicated genome, clustered and highly homologous nature of R genes, as well as recalcitrant to transformation, soybean disease resistance studies is largely lagging compared with other diploid crops. In this review, we focus on the major advances that have been made in identifying both the virulence/avirulence factors of SMV and mapping of SMV resistant genes in soybean. In addition, we review the progress in dissecting the SMV resistant signaling pathways in soybean, with a special focus on the studies using virus-induced gene silencing (VIGS). The soybean genome has been fully sequenced, and the increasingly saturated SNP markers have been identified. With these resources available together with newly developed genome editing tools, and more efficient soybean transformation system, cloning SMV resistant genes, and ultimately generating cultivars with a broader spectrum resistance to SMV are becoming more realistic than ever.